AGGRESSION AND PHYSICAL HEALTH IN MARRIED WOMEN - Shafique, Faiza; Sadiq, Riffat (Journal of Postgraduate Medical Institute, 2020)
Objective: To examine aggression as determinant of physical health in married women. Methodology: The present correlational study was carried out from January to September 2017. One hundred and fifty married women were recruited using snowball sampling method from Jinnah Town, Lyallpur Town, Madina Town And Jaranwala Town of Faisalabad. Demographic Information form, aggression questionnaire and subscale of physical health (quality of life scale) were used for data collection. Cronbach Alpha, Pearson correlation coefficient, linear regression and multiple regression analysis were calculated with SPSS version 20.0. Results: Cronbach's alpha revealed good internal consistency for Urdu Version of Aggression Questionnaire (Î± =0.92). Pearson correlation coefficient has shown significant correlation of Urdu Version with its English (original) Version (r =.69). Linear and multiple regression analyses showed that aggression (p =.001), physical aggression (p =.029) and anger (p =.046) have significantly determined physical health in married women. Conclusion: Physical aggression and anger were detrimental for physical health in married women.